2011
DOI: 10.1158/1538-7445.am2011-2852
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 2852: Lysosomal sequestration of sunitinib may play a role in its resistance

Abstract: Resistance to tyrosine kinase inhibitors (TKIs) is a major clinical problem. Mechanisms that mediate drug resistance include gene mutations, multidrug efflux and activation of alternative growth factor pathways. Sunitinib, a multi-targeted antiangiogenic TKI, has demonstrated clinical efficacy in advanced renal cell cancer (RCC) and gastrointestinal stromal tumors, but is hampered by resistance. In this study we aimed to unravel mechanisms of sunitinib resistance. Based on its large volume of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The nature of the accumulation of these compounds is highly dependent on the degree to which they are lysosomally accumulated, our data demonstrates that sunitinib and crizotinib are in agreement with the physical properties of lysosomal accumulation. For sunitinib, the lysosomal accumulation has also been demonstrated by using its fluorescent properties which co-localized with the Lysotracker, a marker for lysosomes [7]. Moreover, pre-incubation with Bafilomycin-A prevented trapping of sunitinib in the lysosomes [7,16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The nature of the accumulation of these compounds is highly dependent on the degree to which they are lysosomally accumulated, our data demonstrates that sunitinib and crizotinib are in agreement with the physical properties of lysosomal accumulation. For sunitinib, the lysosomal accumulation has also been demonstrated by using its fluorescent properties which co-localized with the Lysotracker, a marker for lysosomes [7]. Moreover, pre-incubation with Bafilomycin-A prevented trapping of sunitinib in the lysosomes [7,16].…”
Section: Discussionmentioning
confidence: 99%
“…For sunitinib, the lysosomal accumulation has also been demonstrated by using its fluorescent properties which co-localized with the Lysotracker, a marker for lysosomes [7]. Moreover, pre-incubation with Bafilomycin-A prevented trapping of sunitinib in the lysosomes [7,16]. Sunitinib achieves very high cellular concentrations since it has been shown that 90% of accumulated drug is held within lysosomes within the cell structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescence Imaging Technique Tissue sections were imaged by an AxioZ1 Imager (Zeiss, Feldbach, Switzerland) with a Fluar 5x/0.25 (magnification/numerical aperture) objective equipped with a cooled, sensitive monochrome camera (Zeiss Axiocam MRm). Fluorescence of sunitinib [12] was acquired using a fluorescent filter (FITC, 50 ms exposure, 16-bit image resolution), together with bright field images. To visualize the amount of sunitinib around beads in the tissue, fluorescent image heatmaps were generated using ImageJ (v1.50a, NIH, Bethesda, MD, USA) Lookup Table "Thermal" by adjusting images to 650-2000 pixel brightness (650 pixel and lower: violet, 2000 pixel and higher: red).…”
Section: Sunitinib Biodistribution By Fluorescence Imagingmentioning
confidence: 99%
“…However, its application has been overshadowed by the emergence of drug resistance. Previous studies have revealed that sunitinib is sequestered in lysosomes as a novel mechanism of drug resistance of ccRCC [26,27]. Therefore, in this study, the relationship between STC2 expression and sunitinib resistance in ccRCC cells was investigated.…”
mentioning
confidence: 97%